DIFFERENTIATED INSTRUCTION FOR EFL CLASSROOM - Suwastini, Ni Komang Arie; Rinawati, Ni Kadek Ayu; Jayantini, I Gusti Agung Sri Rwa; Dantes, Gede Rasben (TELL - US JOURNAL, 2021)
Because each student is unique, the diversity in their ways of learning and speed of learning needs to be considered to help them achieve the best process and outcome. As experts propose differentiated instruction as the method for reaching out to the students’ uniqueness, the present article will elaborate the definition, characteristics, and syntax of differentiated learning in English for Foreign Language context, in order to highlight the strength and weakness of differentiated instruction as proven by previous studies. The present study employed George’s (2008) model of library research, in which the information to support the argument of this article were all derived from secondary sources. As the main argument, the present study adopted the concept of differentiated instruction from Tomlinson (2014), supported with research findings about its implementation taken from articles published in reputable international journal and nationally accredited journals. The study revealed that by its definition and characteristics, differentiated instruction could offer strong benefits for EFL students. However, because the model of instruction needs strong commitment from the school and the teachers since it requires the teachers to adopt several strategies and media meet the different learning styles of the students, which in turn, consumes more time and energy. Thus, for EFL classroom to be benefitted by differentiated instructions, the school and the teachers needs to be fully committed to the committed to its concept, syntax, and its requirements.